2017
DOI: 10.1021/acscatal.7b03298
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous-Phase Acetic Acid Ketonization over Monoclinic Zirconia

Abstract: Heterogeneous catalysis in the aqueous phase is paramount to the catalytic conversion of renewable biomass resources to transportation fuels and useful chemicals. To gain fundamental insights into how the aqueous phase affects catalytic reactions over solid catalysts, vapor- and aqueous-phase acetic acid ketonization over a monoclinic zirconia (m-ZrO2) catalyst had been comparatively investigated using ab initio molecular dynamics (AIMD) simulations and density functional theory (DFT) calculations. The monocli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 59 publications
0
37
0
Order By: Relevance
“…The total amount of adsorbed propionic acid (peak area of 1080 cm −1 ) (A), the amount of monodentate propionate (peak area of 1590-1597 cm −1 ) and bidentate propionate (peak area of 1560 and 1510 cm −1 ) (B) on ZrO2 normalized by surface area. Scheme 2 displays the possible surface reaction of propionic acid ketonization over ZrO2 based on the in situ DRIFTS results and the previous reports [19,25,26]. Propionic acid dissociative adsorbs on the acid-base site as monodentate and bidentate adsorption modes, then forms enolate through α-H abstraction by the vicinal base site.…”
Section: Drifts Study Of Propionic Acid and 3-pentanone Adsorption Onmentioning
confidence: 93%
See 2 more Smart Citations
“…The total amount of adsorbed propionic acid (peak area of 1080 cm −1 ) (A), the amount of monodentate propionate (peak area of 1590-1597 cm −1 ) and bidentate propionate (peak area of 1560 and 1510 cm −1 ) (B) on ZrO2 normalized by surface area. Scheme 2 displays the possible surface reaction of propionic acid ketonization over ZrO2 based on the in situ DRIFTS results and the previous reports [19,25,26]. Propionic acid dissociative adsorbs on the acid-base site as monodentate and bidentate adsorption modes, then forms enolate through α-H abstraction by the vicinal base site.…”
Section: Drifts Study Of Propionic Acid and 3-pentanone Adsorption Onmentioning
confidence: 93%
“…Furthermore, the *C 2 H 5 COO* decreases slowly and there is less contrast with C 2 H 5 COO* after the removal of propionic acid, owing to the stronger binding with catalysts surface. The *C 2 H 5 COO* may even be converted to C 2 H 5 COO*, directly proceeding ketonization, or be desorbed [19,25,26,32].…”
Section: Drifts Study Of Propionic Acid and 3-pentanone Adsorption Onmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of explicit water molecules in the aqueous phase on catalytic reaction have been investigated on both metal and metal oxide surfaces . Desai et al.…”
Section: Introductionmentioning
confidence: 99%
“…Cai et al. comparatively studied vapor‐ and aqueous‐phase acetic acid ketonization over a monoclinic zirconia surface and concluded that the Eley‐Rideal mechanism, instead of Langmuir‐Hinshelwood mechanism, is the major C−C coupling pathway for the formation of β‐keto acid in aqueous phase . The hydrophilic acetic acid molecule/acetate, which was stabilized by surrounding water molecules in aqueous phase, can directly react with the di‐anion species, resulting in β‐keto acid.…”
Section: Introductionmentioning
confidence: 99%